Green Technology Innovation and Its Impact on Financial Performance with the Moderation of Green Image and Green Subsidies in SMEs in Depok City - Maghfuriyah, Alfi; Hertin, Revita Desi; Wijaya, Hadi; Anjara, Febria; Nugroho, Feri; Listiana, Nora; Istiqomah, Nurul Aslamiah (Journal of Environmental Economics and Sustainability, 2024)
This study aims to explore the impact of green technology innovation on the financial performance of SMEs in Depok City, Indonesia. With a focus on green process and product innovations, the research also examines the moderating effects of green image and green subsidies. The study employs Structural Equation Modeling (SEM) to analyze data collected from 387 SMEs, offering insights into the complex relationships between these variables. The results reveal that green process innovation significantly influences green product innovation, which in turn, positively impacts financial performance. The mediating role of green product innovation underscores the importance of integrating process and product innovations for financial success. Additionally, the study finds that a strong green image enhances the positive relationship between green product innovation and financial performance, highlighting the importance of environmental branding. However, contrary to expectations, green subsidies do not significantly moderate the relationship between green product innovation and financial performance.